The use of Lean Methodology to reduce personal protective equipment wastage in children undergoing congenital cardiac surgery, during the COVID‐19 pandemic. Issue 2 (20th December 2020) - Sheehan, John Robert; Lyons, Barry; Holt, Francesca
Abstract: Background: The COVID‐19 pandemic has compounded many existing healthcare delivery challenges including long waiting lists and cost containment. New challenges have arisen, such as demand on supply of personal protective equipment (PPE) and the implications of social distancing on staff, patients, and their families. Despite the pandemic, the need to deliver safe, urgent congenital cardiac surgery has remained. Objective: To demonstrate how Lean methodology can improve PPE supply chain demand and reduce staff exposure to children with unknown SARS‐CoV‐2 status undergoing congenital cardiac surgery, during the COVID‐19 pandemic. Methods: We implemented the define, measure, analyze, improve, and control method (DMAIC) and Value Stream Maps to eliminate waste steps during testing for SARS‐CoV‐2 for children undergoing congenital cardiac surgery. Results: Following a 3‐week period of implementation of this new value stream map, we reduced PPE set usage from 13 to 1 per patient, resulting in an annual saving of over €36, 000 and reducing single‐use plastic waste by nearly 70 000 pieces per annum. We reduced numbers of staff exposed to patients with an unknown SARS‐CoV‐2 status from 13 to 1. Conclusion: The use of Lean methodology can reduce waste of PPE and plastic, resulting in cost savings, while reducing staff exposure when testing patients with congenital cardiac disease for SARS‐CoV‐2. By preventing admission of SARS‐CoV‐2‐positive patients, we can reduce use of isolation beds and prevent cancellation of surgery, improving patient flow and departmental efficiency. Other departments in our institution are implementing similar admission pathways to allow surgical services to restart during the ongoing pandemic.